Assessment of knowledge, attitudes, and perceptions toward flood risk insurance amongst low-income households in South Africa - David Lefutso; Abiodun A. Ogundeji; Gideon Danso-Abbeam; Yong S. Nyam (Climate Services)
South Africa is repeatedly hit by flooding, and it is getting worse with climate change and urbanisation. Applying Knowledge, Attitudes, and Practices (KAP) theory and Protection Motivation Theory (PMT), this study explores low-income households’ perceptions and practices regarding flood risk insurance coverage in East London and Mdantsane-Chalumna. The study involved a data collected from 448 low-income households and applied the Partial Least Square Structural Equation Model (PLS-SEM) to understand the complex relationships between the variables under study. The results show positive attitude toward insurance. However, the knowledge base is critically short. The KAP dimensions are determined by socio-economic factors, for example, education, financial capacity and availability of relevant information; reliance on social grants reduces the perception of relevance of insurance. The adoption is impeded by structural barriers such as low financial literacy, distrust in insurers and administrative complexity. However, there are possibilities to boost financial literacy by means of well-aimed educational campaigns in addition to digital platforms. Subsidised policies and micro-insurance are essential affordable insurance solutions. Equally important is building institutional trust via transparent public–private collaborations and consumer protection mechanisms. Increased adoption will come from simplified mobile platforms and communication strategies that highlight the benefits of insurance and risks of inaction. The findings of this research offer tangible advice for solving both behavioural and structural barriers to the prevention and mitigation of flood risk in South Africa, advancing the debate on flood risk management in the country.